ANTROPOLOGI INTERPRETATIF CLIFFORD GEERTZ: STUDI KASUS KEAGAMAAN MASYARAKAT BALI DAN MAROKO - Nurus Syarifah; Zidna Zuhdana Mushthoza (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
Abstract: This paper discusses Clifford Geertz's thoughts on religion as a cultural system. Geertz is an American cultural anthropologist. According to Geertz, religion and culture are an inseparable unit. Through an interpretative-anthropological approach, Geertz wants to see all religions directly through the eyes of their adherents. This approach is separated from functionalism and reductionism and is more towards an appreciation of the peculiarities of the human dimensions of religion, as well as the ideas, attitudes and goals that arise from these religions. An interpretive anthropological approach is applied by Geertz through a case study in Bali and also a comparison between Indonesia and Morocco. In Bali, Geertz classifies the Balinese religion into traditional religion because this religion contains polytheism, local people's mythology and almost no rational nuances in their theology even though they call it Hinduism. Meanwhile, from the Indonesia-Morocco comparison, Geertz found three differences regarding religious activities, namely the first classical Islamic model. Second, the challenge of the scripturalists. Third, outlook on life and ethos.